Photodynamic and peptide-based strategy to inhibit Gram-positive bacterial biofilm formation - de Freitas, Laura Marise [UNESP]; Lorenzón, Esteban Nicolás; Cilli, Eduardo Maffud [UNESP]; de Oliveira, Kleber Thiago; Fontana, Carla Raquel [UNESP]; Mang, Thomas S. (Taylor & Francis, 2019)
The self-produced extracellular polymeric matrix of biofilms renders them difficult to eliminate once they are established. This makes the inhibition of biofilm formation key to successful treatment of biofilm infection. Antimicrobial photodynamic therapy (aPDT) and antimicrobial peptides offer a new approach as antibiofilm strategies. In this study sub-lethal doses of aPDT (with chlorin-e6 (Ce6-PDT) or methylene blue (MB-PDT)) and the peptides AU (aurein 1.2 monomer) or (AU)2K (aurein 1.2 C-terminal dimer) were combined to evaluate their ability to prevent biofilm development by Enterococcus faecalis. Biofilm formation was assessed by resazurin reduction, confocal microscopy, and infrared spectroscopy. All treatments successfully prevented biofilm development. The (AU)2K dimer had a stronger effect, both alone and combined with aPDT, while the monomer AU had significant activity when combined with Ce6-PDT. Additionally, it is shown that the peptides bind to the lipoteichoic acid of the E. faecalis cell wall, pointing to a possible key mechanism of biofilm inhibition.
Keywords: antimicrobial peptides; Antimicrobial photodynamic therapy; biofilms; Enterococcus faecalis; lipoteichoic acid